Enhanced Biohydrogen Production from Citrus Wastewater Using Anaerobic Sludge Pretreated by an Electroporation Technique - Karim, Ahasanul; Islam, M. Amirul; C. K. M., Faizal; Yousuf, Abu; Howarth, Martin; Dubey, Bipro Nath; Cheng, C. K.; Khan, Maksudur R. (American Chemical Society, 2019)
In the present study, the applicability of electroporation (EP) has been investigated as a pretreatment method for enriching hydrogen producers and eliminating hydrogen consumers in anaerobic sludge (AS). Citrus wastewater was used as a feed source for biohydrogen production. Different treatment intensities (TI) of EP for 0.5 min (TI = 30 kWh/m3), 1 min (TI = 60 kWh/m3), and 2 min (TI = 120 kWh/m3) were employed to observe the effects of EP on the microbial community of AS. Furthermore, sonication with a probe, sonication in a bath, and heat-shock pretreatments were also conducted to compare the hydrogen yield with EP. The cell inactivation was evaluated and visualized using colony-forming units (CFU) and field emission scanning electron microscopy (FESEM), respectively. Among the different TIs, the TI of 60 kWh/m3 achieved higher methanogen inactivation with maximum hydrogen (896 mL) production compared to other EP pretreatments after 180 h of dark fermentation. In comparison with other pretreatments, the highest hydrogen production of 896 mL was achieved with EP treatment, followed by sonication with a probe (678 mL) and sonication in a bath (563 mL). The heat-shock pretreatment exhibited the lowest ultimate hydrogen production of 545 mL among the four different methods applied in this study. The outcome of this study suggests that EP is a promising technique for pretreating mixed cultures for the enhanced production of biohydrogen.